Perception of the Customers TOWARDS GREEN PRODUCTS: An Empirical Study - C. NATARAJAN (International Journal of Psychosocial Rehabilitation, 2020)
Environmental deterioration has become a major societal concern in the modern age. An immediate action by business organizations, governments, and society is required to achieve a balanced growth to achieve socio-economic objectives without scarifying the environment. For many companies, marketing green products is still a matter of risk management. In developing countries, the retailers seem to prefer locally produced products, which are cheaper than imports, but still contribute to local communities. In this context, the present study examined the perception of the customers towards green products in Salem district.By adopting convenience sampling, 750 customers were selected from five municipalities. As an essential part of the study, the primary data were collected with the help of interview schedule. Statistical tools such as student t test, analysis of one-way variance, and percentage analysis were employed. The researcher suggests various measures to improve the scope of green product market.